Relationship Between Sleep Time and Depressive Symptoms in Middle-Aged and Elderly Chinese: Mediating Role of Body Pain - Yang Z; Li B; Ma D; Lv Y; Qiu X; Zhang W; Wang J; Zhang Y; Xu C; Deng Y; Li J; Zhen X; et al. (Psychology Research and Behavior Management, 2025)
Ziqing Yang,1,* Bingsong Li,2,3,* Dan Ma,1,4 Yitong Lv,1 Xinhui Qiu,5 Wenge Zhang,6 Jianye Wang,7 Yanlin Zhang,8 Chunming Xu,9 Yuxin Deng,9 Jinyang Li,10 Xuemei Zhen,2,3 Jun Zhang1 1Department of Orthodontics, School and Hospital of Stomatology, Cheeloo College of Medicine, Shandong University & Shandong Key Laboratory of Oral Tissue Regeneration & Shandong Engineering Research Center of Dental Materials and Oral Tissue Regeneration & Shandong Provincial Clinical Research Center for Oral Diseases, Jinan, Shandong, People’s Republic of China; 2Centre for Health Management and Policy Research, School of Public Health, Cheeloo College of Medicine, Shandong University, Jinan, Shandong, 250012, People’s Republic of China; 3NHC Key Laboratory of Health Economics and Policy Research (Shandong University), Jinan, Shandong, 250012, People’s Republic of China; 4Department of Orthodontics, Shandong Provincial Hospital Affiliated to Shandong First Medical University, Jinan, Shandong, 250021, People’s Republic of China; 5The second Hospital of Shandong University, Jinan, Shandong, 250033, People’s Republic of China; 6School of Management, Shandong University, Jinan, Shandong, 250100, People’s Republic of China; 7Department of Obstetrics and Gynecology, Qilu Hospital of Shandong University, Jinan, Shandong, 250012, People’s Republic of China; 8School of Basic Medical Sciences, Shandong University, Jinan, Shandong, 250012, People’s Republic of China; 9Department of Pediatrics, Xinjiang Medical University, Urumqi, People’s Republic of China; 10Faculty of Nursing, Shihezi University, Shihezi, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xuemei Zhen; Jun Zhang, Email zhenxuemei@sdu.edu.cn; zhangj@sdu.edu.cnObjective: Existing research has yet to adequately examine the correlation between sleep time, body pain, and depressive symptoms. This study seeks to elucidate the interconnections between these three elements.Methods: The study used 2020 CHARLS data for analysis. To assess the intricate association among sleep time, body pain, and depressive symptoms, the study employed Spearman correlation analysis, multiple logistic regression, restricted cubic splines, and mediation effect analysis based on bootstrap testing.Results: Risk factors for depressive symptoms in middle-aged and elderly Chinese include physical pain and reduced sleep duration. Results from the RCS suggest that the lowest risk of depressive symptoms occurs when the sleep time for the middle-aged and elderly population is approximately 7.5 hours. Body pain accounts for a 19.05% mediating effect between sleep time and depressive symptoms, and even after controlling confounding factors, there remains a 7.5% mediating effect.Conclusion: The research findings indicate that there is a significant correlation among sleep time, body pain, and depressive symptoms. Insufficient sleep time and body pain can lead to depressive symptoms. Body pain plays a partial mediating role between sleep time and depressive symptoms.Keywords: middle-aged and elderly people, sleep time, body pain, depressive symptoms